Macroscopic features of the kidneys of fetuses and newborns in preeclampsia: postmortem observational study - Iryna Sorokina; Tetyana Ospanova; Mykhailo Myroshnychenko; Iryna Korneyko (Shahid Sadoughi University of Medical Sciences, 2018)
Background: The state of the mother health is of great importance in the development of children renal pathology. Objective: To reveal macroscopic features of the fetuses and newborns kidneys of the mothers whose pregnancy was complicated by preeclampsia. Materials and Methods: The study involved the kidneys of 106 full-term fetuses and newborns of mothers with physiological pregnancy, complicated pregnancy by preeclampsia. During the autopsies, the shape, texture, surface, color were assessed in each kidney, and then its weight, length, width and thickness were measured. Results: The kidneys in fetuses and newborns from mothers with severe preeclampsia were characterized by a more pronounced lobulation. In fetuses and newborns from mothers with mild preeclampsia, the mass of the left kidney prevailed over the mass of the right kidney. The organometric kidney values were greater in newborns compared to fetuses in the cases of complicated by mild and moderate preeclampsia maternal pregnancy. Conclusion: Maternal moderate and severe preeclampsia delay renal growth in fetuses and newborns that manifest by a reduction of the kidneys organometric parameters.